Factors Influencing the Households’ Adaptation under Natural Disaster Risk in the Coastal Areas of Giao Thien, Giao Thuy, Nam Dinh, Vietnam - Phong, Nguyen Thanh; Mai, Nguyen Ngoc; Aditto, Satit (Jurnal Ekonomi & Studi Pembangunan, 2020)
This research is to identify the impacts of natural disaster risk on households of local residents and to identify the adaptation of households with natural disaster risk in Giao Thien commune, Giao Thuy district, Nam Dinh province, Vietnam. Both qualitative and quantitative methods are applied in this study to assess the overall impact of disasters on the livelihood strategies of households in response to natural disaster. The findings show that the risks of natural disasters affecting the livelihood of the local population in the study area are typhoons, floods, coastal erosion/ sea level rise, and saltwater intrusion. Currently, people in the researching area are not merely affected by one disaster but usually 2-3 or even 4 types of disasters in a short period of time. Therefore, this leads to economic losses, in the form of assets of the households. There are 6 solutions to cope with disaster risks that people often used to reduce the damage include: (1) regularly monitor information; (2) Change season calendar; (3) Change crop varieties; (4) Buy insurance; (5) Save of fertilizer and pesticide inputs; (6) Save seed production.